(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article examines the life and literary activity of Sobir Sayqali, one of the prominent representatives of 18th-century Uzbek literature. The study analyzes the poet’s narratives and epics, his literary heritage, as well as the ideological and artistic features of his works. In order to avoid confusion with other individuals who wrote under the pen name “Sayqali,” the article presents key biographical facts and clarifies their distinctions based on source studies.